Uncovering ancient editing: documented evidence of changes in Joshua 24 and related texts - Mäkipelto, Ville (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2018)
The Hebrew Bible is a product of ancient editing, but to what degree can this editing be uncovered? “Uncovering Ancient Editing” argues that divergent textual witnesses of the same text, so-called documented evidence, should be the starting point for such an endeavor. The book presents a fresh analysis of Josh 24 and related texts as a test case for refining our knowledge of how scribes edited texts. Josh 24 is envisioned as a gradually growing Persian period text, whose editorial history can be reconstructed with the help of documented evidence preserved in the MT, LXX, and other ancient sources. This study has major implications for both the study of the book of Joshua and text-historical methodology in general.